Pengembangan Backend Aplikasi Monitoring Santri Berbasis Web Ppm Al–Azhar Muncar Dengan Metode Iterative Incremental - Fauzi, Daniel Rian; Umam, Khoirul; Haq, Endi Sailul; Suardinata, I Wayan; Suwardiyanto, Devit (Jurnal Informatika dan Komputer, 2025)
At the Modern Islamic Boarding School (PPM) Al-Azhar Muncar, the issues of time and distance between parents and students often hinder the monitoring and communication processes. To address these problems, a web-based student monitoring application for PPM Al-Azhar Muncar was developed. This web-based application will enable effective recording and monitoring of attendance, grades, violations, and student permissions. However, the development of this web-based application faced challenges such as limited time and uncertain feature complexity. As a result, feature development was limited to non-academic areas (Islamic boarding school activities). To overcome the limited time constraint, the research employed the iterative incremental method, which allows for the gradual addition of features and improvements. This method enables the development team to implement and test each feature incrementally in small iterations, allowing usable results to be released earlier, even while other features are still under development. With this approach, development can continue despite the limited available time, as the essential core features can already function properly. This research focuses on backend development using the Laravel framework. The development process went through four iterations, with each iteration comprising the inception, elaboration, construction, and transition phases. During the transition phase, unit testing was conducted. The backend development resulted in features for violations, attendance, permissions, and grading. Testing results indicated that each unit tested, both for valid and invalid cases, met the expected outcomes. Thus, the research was successfully conducted. For future research, the existing features can be expanded to cover academic areas (general education)